REPOSITIONING MADRASAHS IN THE DIGITAL ERA AN ANALYSIS OF GOVERNMENT POLICY ON NATIONAL ELECTRONIC LEARNING - Nurlelah; Aep Saepul Anwar; Dede Ridho Firdaus (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the repositioning of madrasas in the digital era through a review of government policies on the development of national e-learning. The study uses qualitative methods by examining various government policies, particularly the 2019 Islamic Boarding School Law and Regulation of the Minister of Primary and Secondary Education Number 13 of 2025, and their implications for strengthening madrasas as formal educational institutions equivalent to public schools. Data were obtained through literature review and analysis of relevant official documents. The results show that the government has established various strategic policies oriented towards improving access to and quality of education, developing a 21st-century competency-based curriculum, and strengthening religious moderation as the foundation of madrasah education. Although legal recognition of the position of madrasas is increasingly strong, their implementation still faces several challenges, including quality gaps between madrasas, cross-ministerial coordination, and institutional readiness to face digital transformation. Nevertheless, various programs such as the development of a madrasah development roadmap, improving teacher competency, and curriculum modernization demonstrate the government's commitment to strengthening madrasah competitiveness amidst social change and global demands. This study concludes that madrasas have a great opportunity to contribute to the development of superior, character-based, and adaptive Indonesian human resources to the development of the times through integrated policy support and sustainable implementation.